Emergency General Surgery Regionalization: Retrospective Cohort Study of Emergency General Surgery Patients at a Tertiary Care Center. Issue 4 (April 2023) - Ayuso, Sullivan A.; Elhage, Sharbel A.; Cunningham, Kyle W.; Britton Christmas, A.; Sing, Ronald F.; Thomas, Bradley W.; May, Addison K.; Reinke, Caroline E.; Ross, Samuel W.
Background: Emergency general surgery (EGS) patients presenting at tertiary care hospitals may bypass local hospitals with adequate resources. However, many tertiary care hospitals frequently operate at capacity. We hypothesized that understanding patient geographic origin could identify opportunities for enhanced system triage and optimization and be an important first step for EGS regionalization and care coordination that could potentially lead to improved utilization of resources. Methods: We analyzed patient zip code and categorized EGS patients who were cared for at our tertiary care hospital as potentially divertible if the southern region hospital was geographically closer to their home, regional hospital admission (RHA) patients, or local admission (LA) patients if the tertiary care facility was closer. Baseline characteristics and outcomes were compared for RHA and LA patients. Results: Of 14 714 EGS patients presenting to the tertiary care hospital, 30.2% were categorized as RHA patients. Overall, 1526 (10.4%) patients required an operation including 527 (34.5%) patients who were potentially divertible. Appendectomy and cholecystectomy comprised 66% of the operations for potentially divertible patients. Length of stay was not significantly different ( P = .06) for RHA patients, but they did have lower measured short-term and long-term mortality when compared to their LA counterparts ( P < .05). Conclusions: EGS diagnoses and patient geocode analysis can identify opportunities to optimize regional operating room and bed utilization. Understanding where EGS patients are cared for and factors that influenced care facility will be critical for next steps in developing EGS regionalization within our system.